IITA National Youth Service Corp members feature in Sportfest voxpop - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Who knew keeping fit could come with a fun twist? In this lightheaded Vox pop, IITA corpers take on some unexpected questions, from spelling challenges to surprising agricultural facts. Watch their candid reactions, quick wit, and a few hilarious slip-ups.